Exploring the susceptibility of fraudulent financial reporting among government-owned and/or controlled corporations in the Philippines using fraud risk factors with the moderating effect of corporate governance - Alcaraz, Lorian Aliana Polintan (Animo Repository, 2023)
Various news articles and academic journals have highlighted cases of fraud worldwide, prompting researchers to analyze the actions of perpetrators and develop fraud models, identifying eight risk factors: pressure, opportunity, rationalization, capability, arrogance, collusion, external regulatory influence, and COVID-19 pandemic. While most have focused on Indonesia, Ghana, Malaysia, and Vietnam, this research specifically targeted the Philippines to identify the significant fraud risk factors among government-owned and/or controlled corporations (GOCCs) in the country, with the moderating effect of corporate governance. The researchers narrowed down the population and used total enumeration approach focusing on the 31 major GOCCs chosen by the Department of Finance - Corporate Affairs Group (DOF-CAG). Pertinent data were retrieved from the official websites of the GOCCs, Governance Commission for GOCCs (GCG), and Commission on Audit (COA). Descriptive statistics and panel regression analysis were used to analyze the data. Results showed that only pressure, collusion, and rationalization significantly affect the susceptibility of fraudulent financial reporting. The study also found that corporate governance has a statistically significant moderating effect only on the effect of pressure to the susceptibility of fraudulent financial reporting. Based on these findings, the study provided relevant practical and theoretical recommendations.